Supplementation of Avian Semen Extenders with Antioxidants to Improve Semen Quality-Is It an Effective Strategy? - Agnieszka Partyka; Wojciech Niżański (MDPI AG, 2021)
Oxidative stress in sperm is a phenomenon related to the increasing rate of oxidation of cellular components and the excessive production of reactive oxygen species (ROS). The high content of polyunsaturated fatty acids in bird sperm cell membranes renders these cells particularly susceptible to lipid peroxidation (LPO). Therefore, to ensure the proper functioning of cells, it is necessary to have a balance between the formation of ROS and the protective action of the antioxidant system. This review aims firstly to briefly introduce the antioxidant system characteristics of avian semen. Secondly, we summarize the recent knowledge regarding progress in extender supplementation using antioxidants and other compounds to improve avian semen quality parameters and fertility rates. The review focuses on enzymes, vitamins, amino acids, proteins, some plant extracts, and other compounds that can be used to supplement the extenders to reduce the formation of oxidants in poultry semen and maintain its quality and enhance its fertility.